2006
DOI: 10.1111/j.1365-2222.2006.02479.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory atopic disease, Ascaris‐immunoglobulin E and tuberculin testing in urban South African children

Abstract: These results suggest that immune response to Ascaris (Ascaris-sIgE) may be a risk factor of atopic disease in populations exposed to mild Ascaris infection and that MTB infection may be protective against this risk, probably by stimulation of anti-inflammatory networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
3
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 33 publications
3
61
3
6
Order By: Relevance
“…Although a relationship between helminthic infection and allergic diseases has been suspected, whether and how they promote or suppress each other remains controversial. [4][5][6][7][8][9][10][11] Recently, cross-reactivity between Ascaris and HDM antigens the latter of which are a major causative factor in allergic diseases such as asthma, rhinitis, conjunctivitis, and atopic dermatitis, has been reported. [12][13][14][15] In the present study, we immunized rabbits with Ascaris antigens and analyzed the cross-reactivity of the anti-Ascaris antibody to HDM antigens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a relationship between helminthic infection and allergic diseases has been suspected, whether and how they promote or suppress each other remains controversial. [4][5][6][7][8][9][10][11] Recently, cross-reactivity between Ascaris and HDM antigens the latter of which are a major causative factor in allergic diseases such as asthma, rhinitis, conjunctivitis, and atopic dermatitis, has been reported. [12][13][14][15] In the present study, we immunized rabbits with Ascaris antigens and analyzed the cross-reactivity of the anti-Ascaris antibody to HDM antigens.…”
Section: Discussionmentioning
confidence: 99%
“…2) There are controversial reports on the relationship between helminthic infection and allergic diseases. Some of them suggest that helminthic infection promotes allergic disease, [3][4][5][6][7] while others suggest that helminthic infection against allergies has a protective role against allergic diseases. [8][9][10][11] Recent reports describe IgE cross-reactivity between nematode Ascaris and house-dust mite (HDM) allergens in allergic patients, suggesting that Ascaris or HDMs might be a primary sensitizer promoting or modulating sensitization to each other.…”
mentioning
confidence: 99%
“…Ascaris is a nematode affecting approximately 1.5 billion humans, especially in tropical regions, and there are reasons to think that this could influence the natural history of allergic diseases. For example, the infection has been described as a risk factor for wheezing, asthma, severe asthma and sensitization to inhaled allergens [1,2,3,4], and experimental infection with Ascaris suum induces IgE-mediated asthma, histamine release and airway responses after aerosol challenge [5,6]. We found that there are at least 12 IgE-binding components in A. suum extract and identified as tropomyosin a component of 40–42 kDa with intense IgE-binding signals and cross-reactivity with mite extracts [7], suggesting that in order to evaluate the role of A. lumbricoides as risk factor for asthma it is necessary to obtain more information about its allergens.…”
Section: Introductionmentioning
confidence: 99%
“…The next link was the finding that both, helminthiases and allergy, were associated with high levels of total IgE, which was further extended to other features of the immune responses to both processes [65][66][67][68]. This has been followed by epidemiological reports that, using several approaches, have shown that ascariasis is a risk factor for asthma [69][70][71][72][73][74][75][76][77]. However, although there is abundant scientific literature supporting the boosting effect of ascariasis on allergic responses [5, 63- (Table 2), a number of questions remain regarding the mechanisms for inducing an increased allergic response and asthma symptoms in a condition naturally accompanied by immunosuppression (reviewed in [99,100]).…”
Section: The Complex Relationship Between Ascariasis and Allergymentioning
confidence: 99%